Free n-nilpotent dimonoids - Zhuchok, A.V. (Algebra and Discrete Mathematics, 2013)
We construct a free n-nilpotent dimonoid and describe its structure. We also characterize the least n-nilpotent congruence on a free dimonoid, construct a new class of dimonoids with zero and give examples of nilpotent dimonoids of nilpotency index 2.